Characterization of Hepatic Fatty Acids Using Magnetic Resonance Spectroscopy for the Assessment of Treatment Response to Metformin in an Enos−/− Mouse Model of Metabolic Nonalcoholic Fatty Liver Disease/Nonalcoholic Steatohepatitis - Carvalho Da Silva-Xavier, A (John Wiley and Sons Ltd, 2023)
Nonalcoholic fatty liver disease (NAFLD) is the leading cause of chronic liver disease worldwide. Liver biopsy remains the gold standard for diagnosis and staging of disease. There is a clinical need for noninvasive diagnostic tools for risk stratification, follow-up, and monitoring treatment response that are currently lacking, as well as preclinical models that recapitulate the etiology of the human condition. We have characterized the progression of NAFLD in eNOS−/− mice fed a high fat diet (HFD) using noninvasive Dixon-based magnetic resonance imaging and single voxel STEAM spectroscopy-based protocols to measure liver fat fraction at 3 T. After 8 weeks of diet intervention, eNOS−/− mice exhibited significant accumulation of intra-abdominal and liver fat compared with control mice. Liver fat fraction measured by 1H-MRS in vivo showed a good correlation with the NAFLD activity score measured by histology. Treatment of HFD-fed NOS3−/− mice with metformin showed significantly reduced liver fat fraction and altered hepatic lipidomic profile compared with untreated mice. Our results show the potential of in vivo liver MRI and 1H-MRS to noninvasively diagnose and stage the progression of NAFLD and to monitor treatment response in an eNOS−/− murine model that represents the classic NAFLD phenotype associated with metabolic syndrome. © 2023 The Authors. NMR in Biomedicine published by John Wiley & Sons Ltd.